Humidite disponible, periode de vegetation et possibilites d'alerte precoce en cas de famine en Ethiopie - Henricksen, B.L.; Durkin, J.W. (1985)
Estimates moisture availability in Ethiopia since 1953, using a model developed by the FAO; correlates results of the analysis using existing meteorological data with the recorded incidence of drought and famine.